E-BOOK ENSIKLOPEDIA TARI DAERAH DI INDONESIA SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN DI ERA COVID-19 - AYU PRABAWATI; HENI SISWANTARI (Universitas Trilogi, 2022)
Learning in the pandemic era has several recent breakthroughs, one of which is learning online or online. In line with technological advances in the era of the pandemic, learning can be applied with learning media. Utilizing technology in the form of an encyclopedia of regional dance in Indonesia can be an alternative to learning. Previous research explained that the availability of learning media in elementary schools was less varied and the students' motivation was low in learning. The purpose of this study was to determine the quality of regional dance encyclopedia media in Indonesia when applied to learning. This study uses a research and development (R&D) method. Validation was carried out by 4 experts, namely media experts, linguists, learning experts, and material experts. The results of the assessment of regional dance encyclopedia media in Indonesia by media experts scored 86.25 in the